2000
DOI: 10.1111/j.1651-2227.2000.tb00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypo‐osmolar oral rehydration salts solution in dehydrating persistent diarrhoea in children: double‐blind, randomized, controlled clinical trial

Abstract: Our findings suggest that hypo-osmolar ORS has beneficial effects on the clinical course of dehydrating persistent diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
2
0
2
Order By: Relevance
“…Children from Aboriginal communities have an underlying environmental enteropathy, 3,13 so the effect of intestinal solute load would have increased stool fluid losses 17−19 . Studies with oral rehydration solution have found that lower osmolality solutions increase net fluid absorption and diminish diarrhoea 20−23 . This also seems to be true for low‐lactose milk formulas, according to the results of the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Children from Aboriginal communities have an underlying environmental enteropathy, 3,13 so the effect of intestinal solute load would have increased stool fluid losses 17−19 . Studies with oral rehydration solution have found that lower osmolality solutions increase net fluid absorption and diminish diarrhoea 20−23 . This also seems to be true for low‐lactose milk formulas, according to the results of the present study.…”
Section: Discussionsupporting
confidence: 76%
“…(2) Oral Rehydration Therapy Although in general the standard WHO oral rehydration solution is adequate for replacing on-going losses, recent evidence indicates that low osmolality oral rehydration fl uids [41,42] may be advantageous in undernourished children, with no associated risk of hyponatremia. Despite mucosal abnormalities and diminution in digestive and absorptive mechanisms, most children with PD have adequate absorption capacity and tolerate enteral feedings.…”
Section: (1) Initial Resuscitation and Stabilizationmentioning
confidence: 99%
“…Obwohl die WHO-Standardlösung zur oralen Rehydration in der Regel ausreicht, um laufende Flüssigkeits-verluste auszugleichen, lassen Belege neueren Datums darauf schliessen, dass orale Rehydrationsfl üssigkeiten mit niedriger Osmolalität [41,42] bei unterernährten Kindern ohne assoziiertes Risiko einer Hyponaträmie unter Umständen von Vorteil sind.…”
Section: (2) Orale Rehydrationstherapieunclassified